2011
DOI: 10.1037/a0024355
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the effect of cognitive bias modification on anxiety and depression.

Abstract: Cognitive biases have been theorized to play a critical role in the onset and maintenance of anxiety and depression. Cognitive bias modification (CBM), an experimental paradigm that uses training to induce maladaptive or adaptive cognitive biases, was developed to test these causal models. Although CBM has generated considerable interest in the past decade, both as an experimental paradigm and as a form of treatment, there have been no quantitative reviews of the effect of CBM on anxiety and depression. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
577
7
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(654 citation statements)
references
References 111 publications
40
577
7
9
Order By: Relevance
“…reduce the tendency to interpret ambiguous stimuli as threatening). Hallion and Ruscio (2011) found that the interventions reliably led to reductions in attentional and interpretation biases; however, this effect was significantly smaller for ATTs (small effect size) compared with interventions that aimed to modify the interpretation bias. Furthermore, they found that the effect size for the reduction in anxiety following cognitive bias modification was small.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…reduce the tendency to interpret ambiguous stimuli as threatening). Hallion and Ruscio (2011) found that the interventions reliably led to reductions in attentional and interpretation biases; however, this effect was significantly smaller for ATTs (small effect size) compared with interventions that aimed to modify the interpretation bias. Furthermore, they found that the effect size for the reduction in anxiety following cognitive bias modification was small.…”
Section: Discussionmentioning
confidence: 86%
“…Despite these Running Head: ANXIETY, SELECTIVE ATTENTION AND HYPERVIGILANCE positive findings, ATTs are not effective in all individuals with anxiety (see Bar-Haim, 2010). Furthermore, a mixed pattern of results was reported in a recent meta analysis that considered the efficacy of cognitive bias modification in reducing anxiety and depression (Hallion & Ruscio, 2011). In this meta-analysis, cognitive bias modification incorporated studies utilizing ATTs to modify the attentional bias to threat or interventions that aimed to reduce interpretation biases (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that depressed patients might not benefit from attention training procedures to automatize attention away from negative towards positive information. A recent meta-analysis confirms that there is currently no evidence for a beneficial effect of attentional bias retaining using visual cueing paradigms (Hallion & Ruscio, 2011).…”
Section: Attentional Controlmentioning
confidence: 99%
“…Our overall aim was twofold: (a) improve participants’ cognitive functioning in specific, intervention-targeted, neurocognitive functions (emotional reactivity and regulation and executive functions; Dandeneau, Baldwin, Baccus, Sakellaropoulo, & Pruessner, 2007; Etkin, Egner, Peraza, Kandel, & Hirsch, 2006; Hallion & Ruscio, 2011) and (b) reducing PTSD symptoms (secondary target). We hypothesized that gains in emotional reactivity, emotional regulation, and executive functioning might secondarily ameliorate the course of early PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%